Hubungan Penatalaksanaan Antenatal Care (ANC) Dengan Komplikasi Persalinan Di Klinik Pratama Kita Kabupaten Langkat Tahun 2023 - Dewi Sartika Hutabarat; Retno wahyuni; Febriana Sari; Lusiatun Lusiatun; Edi Subroto; Ade Rachmat (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Antenatal care (ANC) visits are contacts between pregnant women and caregivers in terms of assessing the health and well-being of the baby as well as opportunities to obtain information and provide information to the mother and health workers. If a pregnant woman does not have a pregnancy check-up, it will not be known whether her pregnancy is going well or whether she is experiencing a high risk situation and obstetric complications which are dangerous for the life of the mother and fetus and can also cause high morbidity and mortality. The aim of this research is to determine the relationship between Antenatal Care (ANC) Management and Childbirth Complications at the Pratama Kita Clinic, Langkat Regency in 2023. This type of research uses a correlational research method with a cross sectional approach. The subjects of this study were pregnant women, totaling 49 respondents. Retrieval of data using a questionnaire on the management of antenatal care with labor complications. The analysis was carried out univariately and bivariately. The formula in this study uses the Chi Square formula. The management of antenatal care (ANC) is associated with labor complications with a p value = 0.000. The results of the study showed that there was a relationship between antenatal care (ANC) management and birth complications.